Results of extralevator abdominoperineal resection for low rectal cancer including quality of life and long-term wound complications - Welsch, Thilo; Mategakis, Vyron; Contin, Pietro; Kulu, Yakup; Büchler, Markus W.; Ulrich, Alexis (International journal of colorectal disease, 2013)
PurposeExtralevator abdominoperineal resection (APR) for low rectal cancer has been adopted by centers to improve oncological outcome. The present study aimed to investigate oncological results, wound complications, and quality of life (QoL).MethodsPatients who underwent extralevator APR for rectal cancer between 2007 and 2011 were identified retrospectively. QoL status was assessed using the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-CR30 and CR29 questionnaires.ResultsThirty laparoscopic (n = 7) or open (n = 23) extralevator APRs were performed in 17 male and 13 female patients. The mortality was zero; circumferential margin involvement occurred in two cases (6.7 %); and there was no bowel perforation. No local recurrence was noted after a median follow-up of 28.3 months; however, six patients died, and eight developed distant metastases. Perineal wound complications were found in 46.6 % of patients, and all were managed conservatively. Fifty percent of the patients reported persistent perineal pain at the follow-up exam. QoL was assessed 7 to 46 months after surgery, and the global health status (70.6) was comparable to the EORTC reference group and published conventional APR series. The QLQ-CR29 module revealed high mean symptom scores for urinary frequency (48.1), incontinence (30.5), and impotence (79.1).ConclusionsExtralevator APR can control local recurrence but not distant metastases of low rectal cancer. The extended perineal resection appears not to decrease general QoL, but it results in a high rate of perineal wound complications. Genitourinary functions are often impaired, even in the long term, and further improvements to the technique must seek to reduce genitourinary harm.